2000
DOI: 10.1074/jbc.m004082200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Action of Human Apurinic/Apyrimidinic Endonuclease

Abstract: ␤-L-Dioxolane-cytidine (L-OddC, BCH-4556, Troxacitabine) is a novel unnatural stereochemical nucleoside analog that is under phase II clinical study for cancer treatment. This nucleoside analog could be phosphorylated and subsequently incorporated into the 3 terminus of DNA. The cytotoxicity of L-OddC was correlated with the amount of L-OddCMP in DNA, which depends on the incorporation by DNA polymerases and the removal by exonucleases. Here we reported the purification and identification of the major enzyme t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The 3Ј-5Ј-exonuclease activity of normal Ape1 is 2-4 orders of magnitude less than the AP endonuclease activity of Ape1 (19,20). However, Chou et al (32,33) recently demonstrated that Ape1 possesses a specialized 3Ј-5Ј-exonuclease activity that preferentially removes mismatched deoxyribonucleotides at the 3Ј termini of nicked DNA. We find that AN34/Ape1 purified from apoptotic cells possesses enhanced exonuclease activity, which hydrolyzes the 3Ј-DNA terminus from normal deoxyribonucleotides more efficiently than does normal Ape1.…”
Section: Discussionmentioning
confidence: 99%
“…The 3Ј-5Ј-exonuclease activity of normal Ape1 is 2-4 orders of magnitude less than the AP endonuclease activity of Ape1 (19,20). However, Chou et al (32,33) recently demonstrated that Ape1 possesses a specialized 3Ј-5Ј-exonuclease activity that preferentially removes mismatched deoxyribonucleotides at the 3Ј termini of nicked DNA. We find that AN34/Ape1 purified from apoptotic cells possesses enhanced exonuclease activity, which hydrolyzes the 3Ј-DNA terminus from normal deoxyribonucleotides more efficiently than does normal Ape1.…”
Section: Discussionmentioning
confidence: 99%
“…Conserved residues in these enzymes indicate a common catalytic mechanism involving a single metal ion. The 3Ј excision activity of the APEX protein is relatively weak and appears to be influenced by substrate and reaction conditions (37) as well as by the structure of the 3Ј terminal nucleotide (38,39). The structure of the p53 protein is similar to the exonuclease III and APEX proteins (40), and p53 protein is reported to contain 3Ј 3 5Ј exonuclease activity (7).…”
mentioning
confidence: 88%
“…In contrast, the robust AP endonuclease activity of Ape1 is related to the demonstrated roles in BER of exonuclease III in Escherichia coli or Apn1 in yeast (1,13). Recently, it was shown that Ape1 acting as an exonuclease can remove therapeutic antitumor nucleoside analogs incorporated at the 3Ј ends of DNA oligonucleotides, which suggested that Ape1 contributes to cellular resistance to these drugs (20). This work was further extended to show that the exonuclease activity of Ape1 is enhanced on DNA mispairs at the 3Ј termini of nicks and gaps (21).…”
mentioning
confidence: 98%